Molecular docking study of sea urchin (Arbacia lixula) peptides as multi-target inhibitor for non-small cell lung cancer (NSCLC) associated proteins. - Muhammad Hermawan Widyananda; Setyaki Kevin Pratama; Rizky Senna Samoedra; Fikriya Novita Sari; Viol Dhea Kharisma; Arif Nur Muhammad Ansori; Yulanda Antonius (GarVal Editorial Ltda., 2021)
Context: Lung cancer is a type of cancer that causes the most deaths worldwide. The most common type of lung cancer is non-small cell lung cancer (NSCLC). Sea urchin (Arbacia lixula) has high potential as an anti-NSCLC agent. Aims: To analyze the anticancer activity of peptides from A. lixula coelomic fluid in inhibiting the activity of NSCLC-related proteins. Methods: Peptide modeling was performed using the PEP-FOLD3 web server. Proteins that have a crucial role in NSCLC progression were determined using KEGG pathway database. 3D protein structures such as EGFR, PI3K, BRAF V600E, and JAK3 were taken from the RCSB PDB database. Docking was performed using Autodock Vina software. Docking results analysis was carried out using Discovery Studio 2019 software. Results: Some peptides bind to the active sites with low binding affinity. Peptide 10 binds to the active site of the EGFR with a binding affinity of -9 kcal/mol. Peptide 5 binds to the active sites of PI3K and BRAF V600E with binding affinity of -8.2 and -8.1 kcal/mol, respectively. Peptide 11 binds to the active site of JAK3 with a binding affinity of -8.1 kcal/mol. All of these peptides have lower binding affinity than ATP as the native ligand. Besides, these peptides also produce more hydrogen bonds than ATP, so they are predicted to be more stable. Conclusions: Peptides 10, 5, and 11 have high potential as anti-NSCLC agents because they can inhibit the activity of proteins that play an essential role in the growth of NSCLC, namely EGFR, PI3K, BRAF V600E, and JAK3 through the competitive ATP inhibitor mechanism.